2017
DOI: 10.2140/gt.2017.21.1469
|View full text |Cite
|
Sign up to set email alerts
|

Sutured Floer homology and invariants of Legendrian and transverse knots

Abstract: Abstract. Using contact-geometric techniques and sutured Floer homology, we present an alternate formulation of the minus and plus version of knot Floer homology. We further show how natural constructions in the realm of contact geometry give rise to much of the formal structure relating the various versions of Heegaard Floer homology.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…The resulting 4-manifold is exactly W 2 . Hence, from Proposition 2.5 in [15], (7) holds true and we conclude the proof of lemma 3.10. Proof.…”
Section: A Reformulation Of Canonical Mapssupporting
confidence: 69%
See 2 more Smart Citations
“…The resulting 4-manifold is exactly W 2 . Hence, from Proposition 2.5 in [15], (7) holds true and we conclude the proof of lemma 3.10. Proof.…”
Section: A Reformulation Of Canonical Mapssupporting
confidence: 69%
“…The commutativity of ( 1) is guaranteed by the functoriality of the gluing map. The crucial difference from the work of Etnyre, Vela-Vick and Zarev in [7] is that, because of the involvement of closures, the construction of the grading in the monopole and the instanton settings is a delicate issue. We construct a grading in the direct limit in two steps.…”
Section: Outline Of the Proofmentioning
confidence: 93%
See 1 more Smart Citation
“…We will do this in future work. Once we do, we will be able to define a "minus" (or "from") version of KHM by following a scheme of Etnyre, Vela-Vick and Zarev for recovering the "minus" version of knot Floer homology from SF H using bypass attachment maps [7]. In the meantime, we use these handle attachment maps in [1] to prove a monopole Floer analogue of Honda's bypass exact triangle in SF H.…”
Section: Introductionmentioning
confidence: 99%
“…Let K be a framed null-homologous knot in Y . The first author [14] and Etnyre, Vela-Vick, and Zarev [12] showed that the limit of SFH (M, γ n ) along the maps σ + is HFK − (−Y, K). Furthermore, if K is Legendrian, then EH (K) limits to the LOSS invariant L − (K).…”
mentioning
confidence: 99%